The Role of Pro Justitia Principles in Marriage Dispensation Decisions: An Analysis of Legal Certainty in Judicial Decision-Making - Siandi Siandi; Ahmad Habibi; Rinda Rinda (JURNAL ISLAM NUSANTARA, 2026)
Marriage dispensation remains one of the most debated issues in Islamic family law because it places legal certainty, child protection, and judicial discretion in a complex relationship. Although Law Number 16 of 2019 establishes a minimum marriage age, religious courts retain the authority to grant exceptions through marriage dispensation, resulting in varying judicial outcomes. This study aims to analyze the application of the pro justitia principle in marriage dispensation decisions and examine its implications for legal certainty within Islamic family law. The research employs a qualitative, normative-juridical approach, drawing on library research and documentary analysis of statutory regulations, court decisions, and relevant scholarly literature. Data were analyzed through qualitative descriptive-analytical techniques focusing on judicial reasoning patterns and interpretive differences. The findings reveal that pro justitia functions as a substantive interpretive framework guiding judges in balancing statutory requirements, child protection, social realities, and maslahah. Variations in judicial interpretation produce different outcomes despite similar factual circumstances, affecting the predictability of legal decisions. The study concludes that legal certainty depends not only on statutory norms but also on the coherence of judicial reasoning. This research contributes by integrating pro justitia, judicial discretion, legal certainty, and maslahah into a unified analytical framework for understanding marriage dispensation adjudication in Islamic family law.